Reef Landforms Identifications in Sikka, NTT Using Landsat Margery - Asriningrum, Wikanti (Journal of Indonesian Coral Reefs, 2011)
Information on condition and spatial distribution is essentially needed for better coral reef management. In order to provide the information, classifications of reeff morphology s is one way to obtain the physical condition of the reef. This method is relatively straightforward; with the means of remote sensing imageries, because the standard already exists. One of the challenges is what is the best way or detailed steps required to identify these highly variable objects. This exploratory research is aimed to develop identifications criteria of reef morphology s. Sikka district was chosen study area because it has some type of small islands with high diversity of reef morphology s. Each reef morphology s were analyzed to get a general habitat charasteristci which might be relevenat to coral reef management needs. Identificaton was performed visually with geomorphological approach. Indetifications result are qualitative, quantitative and spatial, and presented in teh forms of descrictive elaboration, tabular, and map